MANAGMANAGEMENT AND CONSTRUCTION ENGINEERING OF PAJAJARAN SPORTS CENTER STADIUMMANAGEMENT AND CONSTRUCTION ENGINEERING OF PAJAJARAN SPORTS CENTER STADIUMEMENT AND CONSTRUCTION ENGINEERING OF PAJAJARAN SPORTS CENTER STADIUM - Filbert, Hansel
Since Soekarno’s leadership, there is an eagerness to use sports as the unifier of the nation and as a pride to promote it in Indonesia. The goal of Pajajaran Sports Center Stadium’s construction is that it will revitalize the existing stadium to provide a multipurpose building and a green open space area. Currently, architectural and landscape designs are available, but to exteriorize this project, detailed designs of other technical aspects are required, including the design of management and construction engineering aspects. This final project purpose is to determine the effective and efficient construction methods, setting the project schedule to estimate the time needed for construction and to calculate the project value. The scopes of this final project that will be discussed are preparation works, earthworks, substructure works, superstructure works, and roof structure works. Preparation works that will be conducted are site clearing, temporary fences, project boards, bouwplank construction, mobilization and demobilization and the construction for temporary facilities and utilities. Earthworks that will be conducted are grading, five phases of excavation, soil improvement by grouting, compaction and soil disposal. Substructure works that will be conducted are earth retaining wall using secant piles, earth retaining wall reinforcement using ground anchors, bored pile foundation and raft foundation. Superstructure elements that will be build consists of column, shear wall, beam, slab, and tribune. Roof structure works that will be conducted are base plate works, the assembly and installation of steel roof truss and steel roof truss extension works. Based on the scheduling analysis, the Pajajaran Sports Center Stadium will require at least four hundred and eighty-two days of work. The conceptual cost estimate, which is based on Jakarta International Stadium with 7.000 workers and a GFA of 221.000 m2, is done by counting the ratio of the GFA, construction cost index and inflation rate with Rp782.063.702.597,07 and Rp21.935.978,82 per m2 as the results. The results of the detailed cost estimate which consists of direct costs, indirect costs, profits, and tax is Rp1.229.824.572.859,21 and Rp34.495.151,35 per m2. Note that the cost per m2 may differ significantly because JIS project had more scopes of work (MEP, architectural and others). In this case, the obtained cost per m2 for Pajajaran Sports Center Stadium is larger due to the more conservatively designed substructure work to cope with the clay-shale conditions. The obtained S Curve has a steep part on the substructure works part due to the huge costs it has.